2016
DOI: 10.1371/journal.pone.0149762
|View full text |Cite
|
Sign up to set email alerts
|

PCR-Based Seamless Genome Editing with High Efficiency and Fidelity in Escherichia coli

Abstract: Efficiency and fidelity are the key obstacles for genome editing toolboxes. In the present study, a PCR-based tandem repeat assisted genome editing (TRAGE) method with high efficiency and fidelity was developed. The design of TRAGE is based on the mechanism of repair of spontaneous double-strand breakage (DSB) via replication fork reactivation. First, cat-sacB cassette flanked by tandem repeat sequence was integrated into target site in chromosome assisted by Red enzymes. Then, for the excision of the cat-sacB… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 45 publications
0
11
0
Order By: Relevance
“…Nevertheless, the CRISPR/Cas9 technology has been exploited for a broad range of bacteria and algae. Examples include Escherichia coli , Streptococcus pneumoniae , Bacillus subtilis , B. smithii , Streptomyces spp., Lactobacillus reuteri , L. casei , Clostridium beijerinckii , C. ljungdahlii , C. acetobutylicum , C. cellulolyticum , Pseudomonas putida , Synechococcus elongatus , Actinoplanes sp., Corynebacterium glutamicum , Staphylococcus aureus , and Myxococcus xanthus . These reports have demonstrated that the CRISPR/Cas9 system enables the easy and efficient establishment of point mutations, indels, gene replacements, large gene integrations, and large chromosomal deletions at target genomic loci.…”
Section: Application Of the Crispr/cas System For Microbial Metabolicmentioning
confidence: 99%
“…Nevertheless, the CRISPR/Cas9 technology has been exploited for a broad range of bacteria and algae. Examples include Escherichia coli , Streptococcus pneumoniae , Bacillus subtilis , B. smithii , Streptomyces spp., Lactobacillus reuteri , L. casei , Clostridium beijerinckii , C. ljungdahlii , C. acetobutylicum , C. cellulolyticum , Pseudomonas putida , Synechococcus elongatus , Actinoplanes sp., Corynebacterium glutamicum , Staphylococcus aureus , and Myxococcus xanthus . These reports have demonstrated that the CRISPR/Cas9 system enables the easy and efficient establishment of point mutations, indels, gene replacements, large gene integrations, and large chromosomal deletions at target genomic loci.…”
Section: Application Of the Crispr/cas System For Microbial Metabolicmentioning
confidence: 99%
“…For the second fusion, kan cassette and sacB cassette from the same genomic DNA of MGL1 M were used, named as KS [14]. For the third fusion, the temples for FAR (Fatty acyl-CoA reductase) and cat-sacB are from genomic DNA of MGFARINS and MGKA, respectively, named as FS [7]. Plasmids pMD™18-T Vector, pZS13S, pEASY-Blunt were used to conserve the three fusion fragments EG, KS and FS.…”
Section: Primers Plasmids and E Coli Strainsmentioning
confidence: 99%
“…The constructed pMD-KS was used for seamless deletion of poxB in E. coli strain MGL1 ( Fig. 4) according to our developed method [7]. The kan-sacB cassette was amplified with M13 primers (Table S1), and then, the products were digested with Dpn I and purified.…”
Section: Genome Editingmentioning
confidence: 99%
See 2 more Smart Citations